MBRS-09. EphA3 A NOVEL TUMOUR SPECIFIC THERAPEUTIC TARGET FOR MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Offenhauser, Carolin; Carrington, Benjamin; Thurecht, Kris; Ensbey, Kathleen; Bruce, Zara; Jamieson, Paul; Lim, Yi Chieh; Akgul, Seckin; Li, Michelle; Stringer, Brett; Puttick, Simon; Fuchs, Adrian; et al.
Abstract: Targeted tumour specific therapies for children with medulloblastoma are required to improve survival and reduce the significant long-term side effects associated with current treatment protocols. Our study identifies the receptor tyrosine kinase EphA3 as a tumour specific novel therapeutic target for medulloblastoma and demonstrates safety and efficacy of EphA3-targeting antibody-drug conjugates (ADCs) in preclinical primary medulloblastoma xenograft models. Analysis of published medulloblastoma gene expression datasets shows a significant proportion of medulloblastoma samples across all subtypes have elevated expression of EphA3. Immunohistochemistry staining confirmed positive EphA3 expression in medulloblastoma specimens particularly in the perivascular region, a known stem cell niche. Thus, to target EphA3 in medulloblastoma we developed EphA3-ADCs by conjugating our EphA3-targeting monoclonal antibody IIIA4 to the tubulin-inhibitor maytansine. These EphA3-ADCs were highly effective in vitro and, more importantly, showed significant anti-tumour activity while being well tolerated in vivo in primary orthotopic xenograft models of medulloblastoma. Using intravital bioluminescence imaging we found that treatment with EphA3-ADCs reduced tumour burden of established tumours and, as a corollary, significantly improved survival of these tumour-bearing mice, with a commensurate drop in EphA3 tumour expression levels. We propose that combining EphA3-ADCs with current treatment modalities has the potential to improve outcome and may allow de-escalation of current therapies.